Spiral ganglion neuron degeneration in aminoglycoside-deafened rats involves innate and adaptive immune responses not requiring complement - Gansemer, Benjamin M.; Rahman, Muhammad T.; Zhang, Zhenshen; Green, Steven H. (Frontiers in Molecular Neuroscience, 2024)
Spiral ganglion neurons (SGNs) transmit auditory information from cochlear hair cells to the brain. SGNs are thus not only important for normal hearing, but also for effective functioning of cochlear implants, which stimulate SGNs when hair cells are missing. SGNs slowly degenerate following aminoglycoside-induced hair cell loss, a process thought to involve an immune response. However, the specific immune response pathways involved remain unknown. We used RNAseq to gain a deeper understanding immune-related and other transcriptomic changes that occur in the rat spiral ganglion after kanamycin-induced deafening. Among the immune and inflammatory genes that were selectively upregulated in deafened spiral ganglia, the complement cascade genes were prominent. We then assessed SGN survival, as well as immune cell numbers and activation, in the spiral ganglia of rats with a CRISPR-Cas9-mediated knockout of complement component 3 (C3). Similar to previous findings in our lab and other deafened rodent models, we observed an increase in macrophage number and increased expression of CD68, a marker of phagocytic activity and cell activation, in macrophages in the deafened ganglia. Moreover, we found an increase in MHCII expression on spiral ganglion macrophages and an increase in lymphocyte number in the deafened ganglia, suggestive of an adaptive immune response. However, C3 knockout did not affect SGN survival or increase in macrophage number/activation, implying that complement activation does not play a role in SGN death after deafening. Together, these data suggest that both innate and adaptive immune responses are activated in the deafened spiral ganglion, with the adaptive response directly contributing to cochlear neurodegeneration.